Mensaje “familia humana, comunidad de paz” de Benedicto XVI, Jornada mundial de la paz, 1 de enero de 2008 - Alonso Marcos, Antonio; Corral Salvador , Carlos (UNISCI Discussion Papers, 2008)
In this article there is exposed which idea is across this Message for the World Day of Peace and what it links others that his predecessors have declared, since January 1st, 1968. In it, the Pope offers an overview of the world current situation and penetrates into a series of advises that they make us think over brings over of the gift of the peace and of how working to preserve it and to increase it, speaking in this occasion of the family as community of peace.